2016
DOI: 10.1097/01.sa.0000480666.39724.fd
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Tight Glucose Control Using Hyperinsulinemic Normoglycemia Increases Delirium After Cardiac Surgery

Abstract: Background-Postoperative delirium is common in patients recovering from cardiac surgery. Tight glucose control has been shown to reduce mortality and morbidity. We therefore sought to determine the effect of tight intraoperative glucose control using a hyper-insulinemic normoglycemic clamp approach on postoperative delirium in patients undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…32 Another study indicated that intraoperative tight blood glucose control using hyperinsulinaemic normoglycaemia increases delirium after cardiac surgery. 33 In the present study, a higher baseline blood glucose level was an independent risk factor for PD in elderly patients undergoing THA for hip fracture. As a consequence, we would recommend tight blood glucose control during the perioperative and postoperative periods.…”
Section: Discussionsupporting
confidence: 49%
“…32 Another study indicated that intraoperative tight blood glucose control using hyperinsulinaemic normoglycaemia increases delirium after cardiac surgery. 33 In the present study, a higher baseline blood glucose level was an independent risk factor for PD in elderly patients undergoing THA for hip fracture. As a consequence, we would recommend tight blood glucose control during the perioperative and postoperative periods.…”
Section: Discussionsupporting
confidence: 49%
“…80 Other strategies, including tight control of glucose levels and blood transfusions for delirium prevention in the perioperative setting, have shown varying degrees of benefit. 86,87 Moderate quality evidence suggests that adjusting the depth of anesthesia according to bispectral index monitoring can decrease the incidence of delirium. 60,88 Treatment Nonpharmacologic Approaches-Few recent studies have examined nonpharmacologic approaches for the treatment of delirium.…”
Section: Preventionmentioning
confidence: 99%
“…In contrast, Gandhi et al found a higher risk of death and stroke after tight glycemic control for values of 80‐100 mg/dL. Saager et al even found a higher delirium rate after intraoperative tight glycemic control to maintain levels between 80 and110 mg/dL compared to conventional targets below 150 mg/dL. Overall, there is evidence that tight glycemic control may increase the incidence of hypoglycemia and mortality, which in turn can lead to irreversible brain damage .…”
Section: Discussionmentioning
confidence: 99%